The development of new biomarkers of spermatozoa quality in cattle - Fallon, Lindsey; Diaz-Miranda, Edgar; Hamilton, Lauren; Sutovsky, Peter; Zigo, Michal; Spencer, Thomas E.; Ortega, M. Sofia (Frontiers in Veterinary Science, 2023)
There is a current need for new biomarkers of spermatozoa quality, that consistently and correctly identify spermatozoa that will successfully contribute to subsequent embryo development. This could improve the standardization of semen analysis, decrease early embryo mortality, and use these biomarkers as a selection tool before servicing females. This study utilized imaging techniques to identify potential biomarkers of sperm quality, using sires previously classified as high (n=4) or low (n=4) performing at producing blastocysts in vitro.Spermatozoa were assessed before and following a gradient purification protocol, to understand how populations of cells are impacted by such protocols and may differ between in vivo and in vitro use. Pre-gradient samples from low-performing sires had an increased incidence of DNA damage, although post-gradient samples from high-performing sires were found to have an increased incidence of DNA damage. When evaluating morphology via fluorescent microscopy, the most prevalent defects in pre-gradient samples from high-performing sires were tail defects, which are successfully removed during purification processing. The most prevalent defects in pre-gradient samples from low-performing sires were aggresome defects located in the head, which would be brought into an oocyte upon fertilization and may impair embryo development.Image-based flow cytometry (IBFC) was employed to quantify defect prevalence to evaluate a greater sample size decreasing the variability that exists in manual assessments. Using IBFC, aggresome defects were again identified in the heads of spermatozoa from low-performing sires.Post-gradient samples from low-performing sires had a significantly greater (P <0.05) incidence of aggresome defects than post-gradient samples from high-performing sires. Additionally, IBFC was used to evaluate spermatozoa viability following gradient purification. Distinct populations of sperm cells were identified. High-performing sires had more spermatozoa in the population deemed most viable than low-performing sires. This study demonstrated that spermatozoa defects vary in populations before and following gradient purification, indicating that it may be beneficial to separately evaluate semen for in vivo and in vitro use. Furthermore, a prevalent defect in low-performing sires that could explain a discrepancy between successful fertilization and embryo development was identified. Therefore, elucidating a malfunction regulated by sire, that could potentially affect early embryo development.